Vingança Pornográfica: contextualização do crime - CAMARGO, Gabriel Cargnin (2021)
Revenge pornography has become increasingly popular and well-known, making extensive studies on the subject important. This study aimed to identify the factors that permeate pornographic revenge crime, through a literature review. Virtual crimes are practiced globally, since all countries already have access and use information technology. Revenge pornography is a non-consensual intimate images dissemination in electronic media, recently considered as a crime susceptible to penalty and fine, and the cases are still underreported. It is concluded that, despite the recent advances in Brazilian legislation in regard to cybercrime and revenge porn crimes, there are still failures in protecting network users and in the awareness about the proper technologies use, being fundamental more digital education and research related to the aggressors and victims’ profiles.